Do assorted approaches aid in estimation of uronic acids? Case studies on Tinospora sinensis polysaccharides - Nagar, Shipra (My University, 2014)
Polysaccharides containing uronic acids are of immense biological significance. Colorimetric methods using different chromogens have been explored for uronic acid estimation in polysaccharides but these methods counter numerous difficulties, when neutral sugars are present in substantial amount. The uronic acid content of cold water-soluble polysaccharide (CWSP) and hot water-soluble polysaccharide (HWSP) isolated from Tinospora sinensis, widely known for marked therapeutic significance has been studied. The uronic acid was quantitatively estimated by spectrophotometric methods using carbazole, 3-phenylphenol and 3,5-dimethylphenol (DMP) vis-a-vis gas-liquid chromatography (GLC) analysis. Galacturonic acid in CWSP and HWSP was estimated as 1.41% and 1.20% respectively. The findings bring to light, the efficacy of chromogens and also reveal to what extent, they could be relied upon. The results also indicated higher specificity and selectivity of DMP over carbazole and 3-phenylphenol. However, GLC analysis despite time consuming remains the finest method for precise estimation of uronic acids. Further, GLC analysis of alditol acetates indicated the monosugar composition of L-rhamnose, L-arabinose, D-mannose, D-galactose and D-glucose in molar ratio 0.178, 0.259, 0.140, 1.045 and 98.377 in CWSP and L-rhamnose, L-arabinose, D-xylose, D-mannose, D-galactose and D-glucose in molar ratio 0.608, 0.628, 0.978, 0.227, 0.111 and 97.448 in HWSP respectively.
PUBLISHED
Keywords: Assorted approaches; Colorimetric method; Spectrophotometric methods; Tinospora sinensis; Uronic acid